Optimized Varactor Parasitic Modelling in the Millimeter-Wave Band. - Pérez-Escribano, Mario; Palomares-Caballero, Ángel; Padilla, Pablo; Valenzuela-Valdés, Juan Francisco (My University, 2023)
This work explores the utilization of varactors in the millimeter-wave (mm-wave) band, specifically focusing on their application in voltage-controlled reconfigurable devices. Varactors, or variable capacitors, can adjust capacitance through voltage control, making them ideal for creating rapidly variable systems for radiofrequency (RF) applications. However, parasitic elements in varactors can significantly affect their performance when moving up to the millimeter-wave band and limit their efficiency. Therefore, this work aims to present an optimization approach that accurately calculates the parasitic model for these varactors.
Keywords: Ondas milimétricas; Diodos semiconductores; Broadband characterization; Equivalent Circuit; Millimeter-Wave; Parasitic Modeling; Varactor